PROSES PEMBELAJARAN QUANTUM TEACHING DALAM BAHASA INGGRIS PADA KELAS CO-EDUCATION BERBASIS ADIL GENDER - Hermanto Hermanto (EKSPOSE, 2017)
Quantum as an interaction that converts energy into light. Quantum Teaching meaningful interactions that convert light into energy because all energy is life and diversity in the Teaching process and interdeterminisme contain. The purpose of the Quantum Teaching is to create an effective Teaching environment, creating a fun Teaching process, the brain's ability to adjust to what is needed by the brain, to help improve the life and career success and to help accelerate the Teaching. Errors in understanding the meaning of gender is one factor that led to opposition or difficult to accept gender analysis in solving problems of social injustice. In order to align with the substance of the discussion of the context of Teaching English, Quantum Teaching emphasizes the need of planningn of Teaching conditions (matched) with topic.